2020
DOI: 10.1101/2020.07.23.216622
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The supramolecular landscape of growing human axons

Abstract: During brain development, human axons must extend over great distances in a relatively short amount of time. How the subcellular architecture of the growing axon sustains the requirements for such rapid build-up of cellular constituents has remained elusive. Human axons have been particularly inaccessible to imaging at molecular resolution in a near-native context. Here we apply cryo-correlative light microscopy and electron tomography to growing axonal tracts from human cerebral organoids. Our data reveal a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
(71 reference statements)
2
2
0
Order By: Relevance
“…The narrow tubules were present in 30 tomograms and had undulating shape, where the two lipid bilayers come in contact. This “beaded” morphology is also reported in a recent study of human axons (Hoffmann et al, 2020). In 8 tomograms we found electron dense deposits in the ER lumen (Figure S2A).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The narrow tubules were present in 30 tomograms and had undulating shape, where the two lipid bilayers come in contact. This “beaded” morphology is also reported in a recent study of human axons (Hoffmann et al, 2020). In 8 tomograms we found electron dense deposits in the ER lumen (Figure S2A).…”
Section: Resultssupporting
confidence: 84%
“…While microtubules typically extended beyond the imaged volume, actin filaments were short, with an average length of 250 nm (Figure S1C). Similar to a recent cryo-ET study of human organoid axons (Hoffmann et al, 2020), the observed actin filaments ran roughly parallel to the microtubule network rather than forming rings around the axon shaft. This actin may correspond to “deep” actin which is dynamic and is transported slowly through axons (Chakrabarty et al, 2018; Ganguly et al, 2015).…”
Section: Resultssupporting
confidence: 83%
“…The ultrastructural detail of EM is needed to answer such a question, but decades of EM studies could not discern the submembrane periodic scaffold [2]. It is likely that classical thin-section EM cannot easily contrast actin assemblies made of a few filaments -and more recent cryoEM approaches also failed to visualize the MPS along axons [39,40].…”
Section: Molecular Organization Of the Mpsmentioning
confidence: 99%
“…Developing axons can be subdivided into axon shaft and growth cone. While the former compartment has been proposed to have predominantly a structural role and is enriched in cytoskeletal components and tubular endoplasmic reticulum [105], the latter compartment, which senses and responds to guidance cues, is characterized by a dynamic actin cytoskeleton, the presence of mRNA, polysomes, UPS components, endo-and exocytic vesicles [106,107].…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%